(untitled) (Laisvalaikio tyrimai, 2025)
Topic relevance. An organisation’s reputation is one of the most important factors determining its long-term success and competitiveness in the market. A strong reputation not only helps the organisation attract new customers and partners, but also strengthens consumer trust. Service organisations are sensitive to environmental changes; thus, reputation has experienced various challenges related to scandals, regulatory violations, and public opinion in recent years. Therefore, it is important to assess how an organisation’s reputation is perceived from the consumer’s point of view and what measures could contribute to strengthening its reputation. Research problem. Although an organisation’s reputation is recognised as an essential management and communication tool, there is a lack of a unified theoretical model explaining how various stakeholders perceive and identify an organisation’s reputation, and what cognitive and social processes determine this perception. Practical gap. There is not enough systematic explanation of how different groups (employees, customers, partners, society) interpret the characteristics of the organisation’s activities and form the image of reputation, and what mechanisms they use for this reputation identification. Theoretical context. In many disciplines (public relations, organisational behaviour, social psychology), the processes of reputation perception and identification are studied fragmentarily, therefore there is a lack of synthesis that would allow creating an integral theoretical basis for explaining this phenomenon. Research objective. To create and develop a theoretical disclosure that defines the processes of organisational reputation perception and identification, distinguishing the main concepts, mechanisms and interrelationships. Structural objective. To investigate and analyse the main concepts of reputation perception and identification, to distinguish their attributes, antecedents and consequences, and to create an integrated theoretical basis that reflects the cognitive and social processes of interested parties. Applied objective. To provide conceptual guidelines for further stages of empirical research, allowing for more accurate measurement of the dimensions of reputation perception and identification in organisational research. Research objectives: • To define the theoretical concept of the organisation and the modern organisation. • To identify the significance of organisational reputation and its formation for the organisation. • To reveal the factors influencing the reputation of the organisation on consumer trust in the organisation. Methods. Analysis, synthesis, interpretation, and generalisation of scientific literature. Results. An organisation is a structure in which people or groups of people coordinate their activities to achieve common goals, having a clear hierarchical management system and regulated activities that ensure efficiency and control. Classical organisations usually follow a traditional structure, where decisions are made from the top down, but today’s organisations are increasingly seeking more flexible models that would allow for faster response to changes and promote innovation. Modern organisations are dynamic and able to adapt to a rapidly changing environment, integrating innovations and technologies into their operations. They not only respond to market changes, but also actively initiate them, seeking competitive advantage and long-term growth. Organisational reputation is a dynamic and complex process influenced by many factors, both internal and external. Internal factors, such as organisational culture, values, and employee well-being, are key elements determining an organisation’s reputation, but external factors, such as market dynamics, social responsibility, and innovation, also have a significant impact. Effective reputation management includes both proactive and reactive strategies that help an organisation maintain its positive image and ensure long-term competitiveness. An organisation’s reputation has a significant impact on consumer trust. A well-established reputation helps build long-term relationships with employees, customers, investors, and other stakeholders. Companies that demonstrate transparency, behave ethically, and actively contribute to social responsibility are more likely to receive positive reviews and hold strong relationships with consumers. Trust remains a key factor determining an organisation’s long-term success and competitiveness in the market. Keywords: reputation, organisation, modern organisation, consumer.